2018
DOI: 10.1186/s41606-018-0020-4
|View full text |Cite
|
Sign up to set email alerts
|

A review of sleep disturbances following traumatic brain injury

Abstract: Background: Sleep disorders are common following traumatic brain injury (TBI). Methods: We review the literature regarding sleep disturbances in the acute and chronic phase following TBI in both the adult and pediatric population. Results: Acute and chronic disruption of sleep commonly follows TBI and contributes to morbidity commonly seen post-injury in both adults and children. This includes the direct effect of TBI leading to sleep disruption, as well as sleep disorders resulting from TBI itself. Pre-TBI ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 77 publications
2
14
1
Order By: Relevance
“…The high values of BMI and abdominal circumference in our patients are in line with the results of some previ- ous studies, including the studies by Takatalo et al [17], Samartzis et al [25], and Hangai et al [7], about overweight and abdominal circumference in LDD patients. On the other hand, it disagrees with the results of some other studies like Jones et al [1], Vidman et al [21], and Daneshjoo and colleagues [26].…”
Section: Other Cardiovascular Factorssupporting
confidence: 92%
See 3 more Smart Citations
“…The high values of BMI and abdominal circumference in our patients are in line with the results of some previ- ous studies, including the studies by Takatalo et al [17], Samartzis et al [25], and Hangai et al [7], about overweight and abdominal circumference in LDD patients. On the other hand, it disagrees with the results of some other studies like Jones et al [1], Vidman et al [21], and Daneshjoo and colleagues [26].…”
Section: Other Cardiovascular Factorssupporting
confidence: 92%
“…In addition to loading mechanical pressure on lumbar vertebra [13,14], overweight and obesity are effective in degenerative disc diseases, through biochemical changes [10], effects on lipid profile, vascular and metabolic diseases [8,10], and other known mechanisms. The results of the present study on the lack of physical activity in the subjects under study are in line with the results of the studies by Hengei et al [7], Daneshjoo and colleagues [26], and disagrees with the results of the studies by Stephen et al [27] and Takatalo et al [17] about sport exercises and DD. The results of some studies suggest that regular and continuous physical activity reduces the risk of cardiovascular diseases more effectively compared to sport exercise [8,27].…”
Section: Other Cardiovascular Factorssupporting
confidence: 77%
See 2 more Smart Citations
“…The more frequent mild TBI's are considered as trivial and benign injuries as opposed to less prevalent moderate to severe injuries, which are associated with longlasting consequences for the patients and their environment [3]. Due to the high individual and societal costs associated with extensive rehabilitation needs and chronic disability, moderate to severe TBI represents a critical public health issue [4], with fatigue and sleep problems playing significant roles in the recovery process [5,6]. Between 30% to 70% of the patients experience fatigue [7] and a meta-analysis indicated that 53% experience sleep problems [8].…”
Section: Introductionmentioning
confidence: 99%